MANETs: Overview of Vulnerabilities, Security Threats and Prevention and Detection Techniques - Vora, Kewal; Shah, Jugal; Parmar, Shreyas; Bhattacharjee, Shivani (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad Hoc Network (MANET), because of its decentralized architecture, dynamic topologies and also due to rapid advancement of wireless devices has become a popular area of research. Though the self-configuring characteristic of Ad Hoc network finds application in various domains, they are exposed to vulnerabilities by malicious attackers which might compromise the entire network and reduce the overall performance of the network. These threats need to be dealt; giving rise to various solutions that would not only maintain the network efficiency but also ensure a successful data transmission along with high level of security. Such solution would require detailed information about the vulnerabilities and different type of attacks which would then lead to computing different detection and prevention mechanisms. This paper gives an overview of vulnerabilities of MANETs, different types of threats and discusses various detection and prevention mechanisms against them.